Gandhi's truths in an age of fundamentalism and nationalism - Clarke, Sathianathan; Pickard, Stephen K. (Fortress Press, 2022)
This book examines Gandhi's truths for an age of religious fundamentalism and illiberal nationalism that legitimizes violence and violation. Embedded in the political currents of our day, Gandhi's thought and practice present a religiously plural and inclusive nationalism that is rooted in a universal yet many-sided vision of religious truth.